A systematic review on small-sided games in football players: Acute and chronic adaptations - Bujalance-Moreno, P.; Latorre-Román, P. A.; Garcia-Pinillos, F. (Journal of Sports Sciences, 2019)
Small-sided games (SSG) are played on a small pitch, often using modified rules and involving a smaller number of players. This article aimed to critically analyse the literature to determine how small-sided games affect the performance of football players in the short- and long term. Electronic databases were searched for literature dating from January 2000 to July 2018. The methodological quality of the studies was evaluated using the modified Downs and Black Quality Index (cross-sectional studies) and the Physiotherapy Evidence Database (PEDro) scale (intervention studies). Fifty-three studies, 44 cross-sectional and 9 intervention studies, met the inclusionary criteria for review. Most of the cross-sectional studies focused on describing the differences between SSG protocols, whereas 4 studies focused on making a comparison between "interval" and "continuous" SSG training regimes. On the other hand, intervention studies focused on making a comparison between SSG-based protocols and high-intensity intermittent training (HIIT)-based running protocols, in addition to determine the effect of a SSG-based training programme alone. SSG-based football plans (2 to 4 SSG sessions per week) show athletic performance improvements in football players by improving sprint, repeated sprint ability (RSA) and change of direction (COD) along with muscular and physiological adaptation.